Primary Congenital Glaucoma: An Update - Arshi Singh; Kirti Singh (Delhi Journal of Ophthalmology)
Primary congenital glaucoma is a rare maldevelopment of the eye that affects children in the first few years of their lives. Blindness invariably occurs in untreated individuals. Early diagnosis by detailed examination under anaesthesia followed by prompt treatment is necessary for favourable visual outcomes. Surgery is the primary treatment modality due to limited role of medical management. Visual rehabilitation with management of refractive errors and amblyopia is key for long term visual success. This article gives an overview of the epidemiology, genetics, diagnosis and treatment of this devastating disease.